2005
DOI: 10.1111/j.1349-7006.2005.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of α‐galactosylceramide‐loaded dendritic cells genetically engineered to express SLC/CCL21 along with tumor antigen against peritoneally disseminated tumor cells

Abstract: The close cooperation of both innate and acquired immunity is essential for the induction of truly effective antitumor immunity. We tested a strategy to enhance the cross-talk between NKT cells and conventional antigen-specific T cells with the use of α α α αGalCer-loaded dendritic cells genetically engineered to express antigen plus chemokine, attracting both conventional T cells and NKT cells. DC genetically engineered to express a model antigen, OVA, along with SLC/CCL21 or monokine induced by IFN-γ γ γ γ/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
(72 reference statements)
1
26
0
Order By: Relevance
“…On simulation with a-GalCer, NKT cells rapidly produce large amount of cytokines, resulting in activation of conventional T-cells and NK cells. a-GalCer-loaded DCs are known to be efficient in activation of NKT cells [7,[28][29][30]. We also analyzed the capacity to present a-GalCer and activate NKT cells.…”
Section: Functions and Gene-expression Of Ips-dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…On simulation with a-GalCer, NKT cells rapidly produce large amount of cytokines, resulting in activation of conventional T-cells and NK cells. a-GalCer-loaded DCs are known to be efficient in activation of NKT cells [7,[28][29][30]. We also analyzed the capacity to present a-GalCer and activate NKT cells.…”
Section: Functions and Gene-expression Of Ips-dcsmentioning
confidence: 99%
“…By genetic engineering, we can generate ES-DCs capable of modulating immune response in an antigen-specific manner. Mouse systems have demonstrated the induction of anti-cancer immunity [6][7][8][9][10] and the prevention of autoimmune disease [11,12] by in vivo administration of genetically engineered ES-DCs.…”
Section: Introductionmentioning
confidence: 99%
“…This total was estimated to be at least 160 times more than that of the MC-DCs (without c-Myc transduction). Surface phenotype of PSC-derived cells in the stages of MCs and pMCs The myeloid cells (days [13][14] were a heterogeneous population, almost 90% of which was characterized to be CD11b þ ( Fig. 2A) (Fig.…”
Section: Generation Of Pmcs From Mouse Pscsmentioning
confidence: 99%
“…Previous studies have established methods of generating DCs from PSCs, and demonstrated the utility of PSC-derived DCs in cancer immunotherapy (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, generating a large number of DCs from ESCs or iPSCs has required a scaling-up of the initial volume of undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The studies using mice have demonstrated that in vivo transfer of genetically engineered mouse ES-DC is very effective for modulation of immune responses both positively and negatively. It is possible to induce anti-cancer immunity [4][5][6][7][8][9] and prevent autoimmune disease [10,11] in mouse models with genetically engineered ES-DC. Looking toward the future clinical application of ES-DC technology, a method was developed to generate ES-DC also from human ES cells [12].…”
Section: Introductionmentioning
confidence: 99%